Phase Field Study of Cr-Oxide Growth Kinetics in the Crofer 22 APU Alloy Supported by Wagner’s Theory - Kai Wang; Robert Spatschek (Energies, 2023)
The Crofer 22 APU alloy is a frequently used metallic material to manufacture interconnects in solid oxide fuel cells. However, the formation and evaporation of Cr<semantics>2</semantics>O<semantics>3</semantics> not only increases the electrical resistance but also leads to the Cr-related degradation over the service time. In order to investigate the growth kinetics of Cr-oxide, i.e., Cr<semantics>2</semantics>O<semantics>3</semantics>, the multi-phase field model coupled with reliable CALPHAD databases is employed. The phase field simulation results are benchmarked with the predictions of Wagner’s theory. Moreover, we evidence the influence of the temperature and Cr concentration on the ferritic matrix phase and the oxygen concentration at the Cr<semantics>2</semantics>O<semantics>3</semantics>/gas interface on the growth kinetics of Cr-oxide, paving the way for further investigations of Cr-related solid oxide fuel cell degradation processes.